The Effect of Total Quality Management (TQM), Corporate Culture, and Information Technology on Corporate Performance with Business Process Management as a Mediation - Muh Risal; Musran Munizu; Andi Aswan (Magister Management, Hasanuddin University, 2021)
The aim of the research is to examine the effects of total quality management, corporate culture, and information technology on corporate performance with the mediating variable of business process management. It is conducted at PT PLN (Persero) UP3 Palopo by taking a sample of 96 respondents. Sampling using the proportional random sampling method. Primary data collection using a survey method with questionnaires. This kind of research is a quantitative approach with the use of the path analysis method. The research found that TQM and IT have a positive effect on business process management, while corporate culture shows an insignificant score. TQM and corporate culture indicate a positive and significant effect on corporate performance, but IT did not. TQM shows a positive and significant score on corporate culture through business process management. However, corporate culture and IT did not indicate a significant relationship.